Visual Implicit Pre-Cueing Improves Response Time in Decision-Making in Dyslexic Children - Barela, José A. [UNESP]; da Silva, Crislaine [UNESP]; de Jesus, Paola R. [UNESP]; Figueiredo, Gabriella A. [UNESP]; Barela, Ana Maria F.; Novak, Andrew R.; Fransen, Job (Wiley, 2024)
This study aimed to examine the effect of visual pre-cueing presented at different time intervals in the response time of dyslexic and non-dyslexic children. Fifteen dyslexic and 15 non-dyslexic children performed a computerised four-choice reaction time task across four conditions: no pre-cue and a 43-ms time interval (or duration) of a centralised dot appearing in the stimulus circle at 43, 86 or 129 ms prior to the stimulus. Each condition was repeated eight times, totaling 32 trials, and presented in a random order. Response correctness and response times were recorded for each trial, and z-scores were obtained by standardising performance in the three pre-cued conditions relative to the no pre-cue condition. Dyslexic children took longer to respond in the task than non-dyslexic children. Both dyslexic and non-dyslexic children had faster response times in the pre-cued conditions than in the conditions without the pre-cue. These lower response times were inversely correlated with the length of the pre-cueing interval. These results suggest that dyslexic children use visual pre-cueing to improve decision-making. The ability of dyslexic children to use pre-cues may offer an interesting avenue for the exploration of interventions aimed at minimising behavioural and cognitive difficulties resulting from dyslexia.
Keywords: dyslexia; implicit cues; reaction time